Pengaruh Harga Minyak Dunia, Inflasi, Konsumsi Rumah Tangga terhadap Pertumbuhan Ekonomi Indonesia - Ulin Nuhaella Almaya; Wahyu Hidayat Riyanto; Syamsul Hadi (Jurnal Ilmu Ekonomi, 2021)
This study aims to determine the effect of world oil prices, inflation, household consumption on economic growth in Indonesia. This research is a type of descriptive research with a quantitative approach using the annual time series data in 1988 - 2018. The model analysis technique used in this study is multiple linear regression with 31 samples. The results showed that both simultaneously (F test) and partially (t test) world oil prices had a significant (positive) effect, inflation had a significant (negative) effect, and household consumption had a significant (positive) effect on economic growth. Based on the results of the study, the government as a joint policy maker with Bank Indonesia can jointly reduce and maintain the stability of the inflation rate through monetary policy so that economic actors get clarity and encourage productivity by opening investment taps, providing business protection, and lowering export duties or create a fiscal policy. The government needs to establish policies to encourage oil production so that oil production can be optimal dan maintain oil supply so that people’s needs are met and oil prices can remain stabl and also maintaining the stability of prices for goods so as to encourage domestic consumption.